PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION (RME) DENGAN MODEL PEMBELAJARAN CERAMAH DI SD ISLAM AL-ABROR KELAS V SEMESTER I TAHUN PELAJARAN 2015/2016 - Sri Windaningrum; Vidya Pratiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
This research is motivated by the low result of fifth grade students learn mathematics, as indicated by the value of the majority of students who have not reached the minimum completeness criteria (KKM). It is alleged inaccuracy of strategies and learning model that led to student learning outcomes less than the maximum or less good. As the use of active learning. The problem of this study is whether there is a difference in student learning outcomes using model Realistic Mathematic Education (RME) with a lecture learning model in SD Islam Al-Abror class V. The purpose of the problems to be achieved is to determine the differences in student learning outcomes using model Realistic Mathematic Education (RME) with a lecture learning model in SD Islam Al-Abror class V. This research is a quantitative experimental research. The population in this study were all students of class V SD Islam Al-Abror with the number of 67 students. Samples taken as many as 46 students using random sampling techniques. The research data is data of student learning outcomes and data on the observation application of the model. Data obtained through the learning outcomes of the evaluation value and Post Test instrument in the form of multiple choice questions that cover the indicators corresponding to the content standards. Observation data model application obtained through observation instruments. The study design used is a post-test Only Control Group Design. Theoretical hypothesis proposed in this study is a significant difference between the mathematics learning outcomes of students who take the learning model of learning Realistic Mathematics Education (RME) with students who take the learning in the classroom lecture learning model V. And working hypothesis is that there is no difference Mathematical significant learning outcomes among students who follow the teaching learning model Realistic Mathematics Education (RME) with students who take the learning in the classroom lecture learning model V. Based on the analysis of data, obtained tcount 15.277 ttable value greater than 1.680 at significance level of 5 %. The final result of the average value of post test the experimental class of 78 and the control class is 56. So the hypothesis is accepted. And it can be concluded that "there are significant differences between the mathematics learning outcomes of students who take the learning model of learning Realistic Mathematics Education (RME) with students who follow the teaching learning model lectures in class V